SCIENTIFIC INTERPRETATION STUDY: AL JAWAHIR'S REVIEW OF THE INTERPRETATION OF THE QUR'AN ON THE COMPOSITION OF THE EARTH ELEMENTS IN ADAM'S BODY - Sufian Suri; Irwanto Irwanto; Sayed Akhyar; Andri Nirwana AN (Universitas Muhammadiyah Surakarta, 2022)
Humans are formed from the process of evolution according to Charles Darwin. The process of the creation of humans from the point of view of the theory of evolution put forward by a famous scientist named Charles Robert Darwin, who stated that humans were the evolution of ape species or a kind of short-tailed monkey. there is a book entitled 'On The Origin of Species by Means of Natural Selection, or The Preservation of Favored Racesin The Strungle for Life' which states that humans came from a revolutionary ape species from a very long time ago. Darwin's theoretical paradigm in biological knowledge today is the basic reference in every theory carrying the origin of the development of life (organisms). Even though there are many verses of the Qur'an that mention the elements that make up Humans in several verses. This study aims to criticize the theory. The research method used in this research is a systematic literature review. The results of this study The creation of soil according to Tanthawi, went through the following stages, turab (Ali-Imran: 59), clay mixed with water (al-An'am: 2), then became thin lazib (As-Shaffat: 11), then processed into black mud (hammain) (Al-Hijr: 26), then became dry clay like pottery (ar-Rahman: 14), after that it turned into pottery (fakhkhar) ar-Rahman: 14, then became Adam as the first human , in the interpretation of the Ministry of Religion, through stages starting from soil, starch essence comes from soil (al-Mu'minun: 12), dry clay from shaped mud (al-Hijr: 26 ), and dry soil such as pottery. (Ar-Rahman:14).Manusia terbentuk dari Proses Evolusi menurut Charles Darwin. Proses terciptanya manusia dari sudut pandang teori evolusi yang dikemukakan oleh seorang ilmuwan yang terkenal bernama Charles Robert Darwin, yang menyatakan manusia adalah evolusi dari spesies kera atau sejenis monyet berekor pendek. ada sebuah buku yang memiliki judul ‘on The Origin of Species by Means of Natural Selection, or The Preservation of Favoured Racesiin The Strunggle for Life Yang menyatakan bahwa manusia berasal dari spesies kera yang revolusi dari waktu yang sangat lama. Paradigma teori Darwin dalam pengetahuan biologi dewasa ini menjadi rujukan dasar dalam setiap teori-teori mengusung asal-usul dari perkembangan kehidupan(organisme). Padahal banyak ayat al qur’an yang menyebutkan tentang elemen elemen pembentuk Manusia di beberapa ayat. Penelitian ini bertujuan untuk mengkritik Teori tersebut. Metode penelitian yang digunakan dalam riset ini adalah systematic literature review. Hasil dari penelitian ini Penciptaan tanah menurut Tanthawi, melewati tahapan sebagai berikut, turab (Ali-Imran: 59), tanah liat bercampur air (al-An'am: 2), kemudian menjadi lazib tipis (As-Shaffat: 11), kemudian berproses menjadi lumpur hitam (hammain) (Al-Hijr: 26), kemudian menjadi tanah liat kering seperti gerabah (ar-Rahman: 14), setelah itu berubah menjadi gerabah (fakhkhar) ar-Rahman: 14, kemudian menjadi Adam sebagai manusia pertama, dalam tafsir Kemenag, melalui tahapan mulai dari tanah, saripati pati berasal dari tanah (al-Mu'minun: 12), tanah liat kering dari lumpur berbentuk (al-Hijr: 26 ), dan tanah kering seperti gerabah. (Ar-Rahman:14)